2021
DOI: 10.1063/5.0043498
|View full text |Cite
|
Sign up to set email alerts
|

Cation effect of inorganic salts on ionic Seebeck coefficient

Abstract: Ionic thermoelectric materials attract widespread attention due to their large Seebeck coefficient compared with electronic thermoelectric counterparts whose main charge carriers are electrons or holes. The present work shows that the ion-polymer matrix interaction can alter the Seebeck coefficient to a great extent. To further shed light on the role of ions, seven water-soluble inorganic chlorides are utilized in this work, to highlight the influence of the cationic softness parameter on the Seebeck coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…13 Under a temperature gradient for ionic conductors, this effect can produce positive or negative thermovoltages according to the charge type of the major ionic species (cation or anion), respectively, which is an important characteristic in iTEs for practical applications such as iTE modules with series connection. 11 However, there have been few reports for iTE materials with negative ionic Seebeck coefficient (S i ), 11,[14][15][16][17][18][19][20] because of the difficulty in controlling anion transport and the low diffusivity of anions rather than cations due to the large anion size. Nonetheless, the PF for ionic polymers could be dramatically enhanced by taking advantage of a high S i value from ion channel control in the hydrogel matrix and easy carrier-ion tuning.…”
Section: Introductionmentioning
confidence: 99%
“…13 Under a temperature gradient for ionic conductors, this effect can produce positive or negative thermovoltages according to the charge type of the major ionic species (cation or anion), respectively, which is an important characteristic in iTEs for practical applications such as iTE modules with series connection. 11 However, there have been few reports for iTE materials with negative ionic Seebeck coefficient (S i ), 11,[14][15][16][17][18][19][20] because of the difficulty in controlling anion transport and the low diffusivity of anions rather than cations due to the large anion size. Nonetheless, the PF for ionic polymers could be dramatically enhanced by taking advantage of a high S i value from ion channel control in the hydrogel matrix and easy carrier-ion tuning.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the obtained Seebeck coefficient is basically on the order of mV K –1 , which shows a broad prospect in low-grade heat harvesting . Currently, much research on i-TE systems has been reported based on ionic liquids, polyelectrolytes, and inorganic salt–polymers. Unfortunately, the ionic conductivity of these systems is several orders of magnitude lower than that of normal electronic conductors.…”
mentioning
confidence: 99%
“…Many p-type iTE materials have been reported previously. 11,[13][14][15]17 However, there are few reports on n-type iTEs 16,18,19,[21][22][23][24] because of the difficulty in controlling anion carrier transport and the lower diffusivity of anions in comparison with cations due to their larger size, which disturb sufficient ion diffusion in ionic conductors. As an example, the polymer gel of poly(vinylidene fluoride-co-hexafluoropropylene)/1-ethyl-3-methylimidazolium bis (trifluoromethylsulfonyl)imide ([EMIM][TFSI]) with an 80 wt% ionic liquid content was reported as an n-type iTE film with an S of À4.0 mV K À1 .…”
Section: Introductionmentioning
confidence: 99%